Effectiveness of the Think Pair Learning Model, Experimental Method on Learning Outcomes of Class III Students in Kota Padang State Elementary Schools - Metha Lubis; Fahmiya Azlin (CV. Get Press Indonesia, 2024)
Through collaborative problem-solving and critical thinking, students engage in the Think-Pair-Share approach, or